IMPLEMENTASI STRATEGI PEMBELAJARAN KOOPERATIF (COOPERATIVE LEARNING) TIPE JIGSAW DI PERGURUAN TINGGI - Triani, Dewi Agus (IAIN Kediri, 2016)
Cooperative learning is a learning that asks students to work in group to solve problems given. Jigsaw is one of method in cooperative learning strategy that gives students space to learn actively by optimizing their potentials and responsible to their team. This article consists of explanation on cooperative learning strategy-jigsaw type that can be applied in higher education, especially Islamic higher education. Cooperative learning strategy-jigsaw type can give contribution toward teaching in higher education in order to un-dominated learning by lecturer that makes the students tend to be passive getting and memorizing materials from the lecturer. The implementation of cooperative learning strategy-jigsaw type will add teaching variation for lecturer and make the students become more creative in building their knowledge.Keywords;cooperative learning, Jigsaw, higher education, creativity